CHARACTERIZATION OF EGGPLANT ENDOPHYTE BACTERIA AND RHIZOBACTERIA AS WELL AS THEIR ANTAGONISTIC ABILITY AGAINST Ralstonia solanacearum - Saridewi, Larasati Puspita; Prihatiningsih, Nur; Djatmiko, Heru Adi (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2020)
Characterization of eggplant endophyte bacteria and rhizobacteria as well as their antagonistic ability against Ralstoniasolanacearum. Bacterial wilt caused by Ralsonia solanacearum is one of important diseases causing severe loses in eggplantproduction. Various strategies were used to manage bacterial wilt, including planting resistant varieties, soil amandement, andsoil solarization. However, management of R. solanacearum in eggplant by using endophytic bacteria and rhizobacteria werenot been done that much. The objective of this study was to: (1) characterization of endophytic and rhizobacteria; (2)determines the inhibition ability of endophytic and rhizobacteria isolates against R. solanacearum pathogen on eggplant. Thelaboratory experiment was arranged in completely randomized design with 5 treatments and 5 replications. The double layermethod using yeast peptone glucose agar (YPGA) medium was used in vitro test. Based on the morphological characteristicsthese isolates were suspected as a member of genus Bacillus. Among the isolates used in this study, TK isolate showed thebest capability to inhibit growth of R. solanacearum.